2023
DOI: 10.1186/s12890-023-02635-w
|View full text |Cite
|
Sign up to set email alerts
|

The utility of long non-coding RNAs in chronic obstructive pulmonary disease: a comprehensive analysis

Qi Lin,
Chaofeng Zhang,
Huixin Weng
et al.

Abstract: Objectives Chronic obstructive pulmonary disease (COPD) is one of the main causes of morbidity and mortality in the world. However, there are some patients who are not diagnosed early and correctly through routine methods because of inconspicuous or serious symptoms. This study aims to assess the diagnostic role of long non-coding RNA (lncRNA) in COPD. Methods We searched literature from electronic databases, after excluding non-COPD literature, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…All these findings suggested that MitoQ reversed the increase in ROS and the mitochondrial damage caused by PM2.5, thereby inhibiting mitochondrial-mediated apoptosis. Recent studies had indicated that non coding RNA (ncRNA) participated in variety of physiological and pathological processes after PM 2.5 expression, and the expression of ncRNA change during pulmonary diseases ( 31 , 32 ). MitoQ can maintain mitochondrial metabolism and dynamic stabilization through affecting the expression of ncRNAs ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…All these findings suggested that MitoQ reversed the increase in ROS and the mitochondrial damage caused by PM2.5, thereby inhibiting mitochondrial-mediated apoptosis. Recent studies had indicated that non coding RNA (ncRNA) participated in variety of physiological and pathological processes after PM 2.5 expression, and the expression of ncRNA change during pulmonary diseases ( 31 , 32 ). MitoQ can maintain mitochondrial metabolism and dynamic stabilization through affecting the expression of ncRNAs ( 34 ).…”
Section: Discussionmentioning
confidence: 99%